Concordance of self‐reported practice patterns of American Rhinologic Society members with the International Consensus Statement of Allergy and Rhinology: Rhinosinusitis. Issue 5 (27th February 2020) - Riley, Charles A.; Zheng, Zhong; Williams, Nicholas; Smith, Timothy L.; Orlandi, Richard R.; Tabaee, Abtin
Abstract : Background: The 2016 International Consensus Statement on Allergy and Rhinology: Rhinosinusitis (ICAR:RS) is a collaborative distillation of available research and consensus recommendations for the management for chronic rhinosinusitis (CRS). However, implementation of the ICAR:RS recommendations in the reality of clinical practice is not clearly defined. Methods: An anonymous, web‐based survey of the American Rhinologic Society membership was performed in October, 2018. Respondents were asked about the frequency that they recommended the various treatments reviewed in ICAR:RS in the context of medical management for CRS. A 7‐point Likert‐type scale assessed the frequency of treatment patterns. Results: A total of 140 members completed the survey (response rate 11.9%). Seventy‐two (51.4%) were in practice for 0 to 15 years, 61 (43.6%) completed a rhinology fellowship, and 73 (52.1%) worked in private practice. Disparate treatment patterns were reported for each of the therapies assessed for CRS, including those that were "recommended" or "recommended against" in ICAR:RS. Members with <15 years of experience were more likely to use nasal saline irrigation. Fellowship‐trained respondents reported a greater likelihood of using nasal saline irrigation and aspirin desensitization (for patients with aspirin‐exacerbated respiratory disease). Practitioners in academic medicine were more likely to utilize aspirin desensitization than those in private practice. Surgeons performing >100 sinus surgeries per year were more likely to use topical antibiotics. Conclusion: The range of reported treatment patterns identified in this study despite the availability of the ICAR:RS recommendations may suggest the need for improved standardization of CRS management.